الأوراق التجارية الإلكترونية - منزول, يمينة (Ibn Khaldun University of Tiaret, 2024)
يعد موضوع الأوراق التجارية الإلكترونية من المواضيع القديمة الحديثة بتطورها من حيث آليات معالجتها وإنشائها والوفاء بها إلكترونيا، لذلك لا يمكن ا عتبارها من ضمن وسائل الوفاء الحديثة في المجال التجاري والمصرفي، وإنما طورت بتطور تقنيات الكتابة والتوقيع، وطورت كذلك إستجابة لمحاكاة الرقمنة مختلف القطاعات التجارية والمصرفية. لذا تهدف دراسة موضوع الأوراق التجارية الإلكترونية إلى الوقوف عن مدى استجابة التشريعات الدولية والوطنية لمتطلبات الرقمنة، ووضع تنظيم قانوني تبرز من خلاله الخصوصية الإلكترونية في الأوراق التجارية من جهة، دون المساس بالوظائف الأساسية أو المبادئ التي يرتكز عليها قانون الصرف وإمكانية توافق أحكام قانون الصرف التقليدية مع رقمنة الأوراق التجارية وقابليتها للتطبيق عليها من جهة أخرى مع إلزامية البحث عن الأطر الحمائية التشريعية المنتهجة للأوراق التجارية الإلكترونية، دوليا ووطنيا مدنيا وفنيا وجنائيا بما يكفل التعامل ا لآمن بها The subject of electronic commercial papers is considered one of the old and modern topics in terms of its development in terms of mechanisms for processing creating, and fulfilling it electronically. Therefore, it cannot be considered among the modern means of fulfillment in the banking field. Rather, it was developed with the development of writing and signing techniques, and it was also developed in response to the simulation of digitization in various commercial and banking sectors. Therefore, the study of the issue of electronic commercial papers aims to determine the extent to which international and national legislation responds to the requirements of digitization, and to develop a legal regulation through which electronic privacy in commercial papers is highlighted on the one hand, without prejudice to the basic functions or principles on which the exchange law is based and the possibility of compatibility of the provisions of the traditional exchange law with The digitization of commercial papers and their applicability to them, on the other hand, along with the obligation to search for the legislative protective policy adopted for electronic commercial papers, internationally and nationally civilly, technically, and criminally, in a way that ensures safe dealing with them.

المسؤولية الجزائية لمصفي الشركات التجارية - مرجي, نفيسة (Université Abd El Hamid Ibn Badis Mostaganem, 2024)
مــلخص مذكرة الماستر تحتل الشركات التجارية في العصر الراهن أهمية بالغة في بناء وتنمية اقتصاد الدول، بحيث أصبحت تشكل دعامة لاستقرارها الاقتصادي، ولقد حظيت باهتمام المشرع الجزائري فنظم حياة الشركة في مختلف مراحلها بداية من تأسيسها وتسييرها إلى غاية انقضائها . إن الشركة باعتبارها شخصا معنويا تتأسس وتباشر نشاطها لتحقيق الغرض الذي أنشئت من أجله، فإنها معرضة لانقضائها ولحلها لأي سبب من أسباب الانقضاء، فتنتهي الرابطة القانونية التي تجمع بين الشركاء وتدخل في مرحل التصفية

الحق في الحبس كضمان للبائع في عقد البيع - القادر, بركان عبد; ياسين, مهدي (جامعة مولود معمري تيزي وزو, 2024)
يتميز مجال العقود والالتزامات بأهم عنصر من وهو التقابل والتماثل في الحقوق والواجبات التي ترد على كل طرف، غير أنه من بين الحقوق التي يتمتع بها الطرف المتعاقد في حال تقاعس الطرف المتعاقد معه عن التنفيذ أو الامتناع عن ذلك، هو ممارسة الحق في الحبس سواءً كان الحابس بائعاً أو مشتري. يرد الحق في الحبس على كافة الأشياء التي تكون قابلة للحجز والتنفيذ، ولعل عدم قابليته للتجزئة يعد من أهم الخصائص التي تجعل منه ضمانة حقيقية للوفاء بالديون أو لأداء الالتزامات المتفق عليها بموجب العقد. يندرج الحق في الحبس ضمن الوسائل الدفاعية للدائن يلجأ إليها تجاه المدين، وفق ما نص عليها القانون من جهة، وما تم الاتفاق عليه في العقد من جهة أخرى، حيث يتطلب هذا الحق في وجوده توفر مجموعة من الشروط، ويترتب عن إعماله العديد من الآثار القانونية السارية على أطراف العلاقة التعاقدية، وينقضي بوسائل شتى تندرج من حيث الأهمية والأولوية في التطبيق بين الأصل والاستثناء.
Keywords: Bien immobilier; Bien meuble; Chose vendue; Créanciers; Droit accessoire; Droit de rétention; Exception d'inexécution; Exécution; Possession; Prix dû; Renonciation; Sûreté adéquate; التأمين الكافي; التنازل; الثمن المستحق; الحق التبعي; الحق في الحبس; الحيازة; الدائنين; الدفع بعدم التنفيذ; الشيء المبيع; العقارات; المنقولات; الوفاء

التضامن الصرفي في الأوراق التجارية - قلتة, محمد الأمين; بن شاعة, براهيم (Ibn Khaldun University of Tiaret, 2024)
يعد التضامن مبدأ من مبادئ القانون التجاري، وأحد أهم الضمانات التي يعتمدها قانون الصرف من أجل حصول حامل الورقة التجارية على قيمتها عند ميعاد استحقاقها، إذ يحق لهذا الأخير الرجوع على أي موقع أو على جميع الموقعين بكامل قيمة الورقة التجارية. تعد الأ وراق التجارية من وسائل الدفع التي تقوم مقام النقود في الوفاء، فهي تؤدي نفس الوظيفة التي تؤديها النقود، كما وأنها قابلة للتداول، ونظرا لأهمية هذه الأوراق في المعاملات التجارية ولكي تقوم فعلا مقام النقود في الوفاء فقد أحاطها المشرع الجزائري بمجموعة من الضمانات حماية للثقة والائتمان القائم بين التجار،ويعتبر التضامن الصرفي من أهم هذه الضمانات؛ إذ يحمي حامل الورقة التجارية ويشعره بالأمان والطمأنينة، والذي يجعل كل موقع عليها ضامنا للوفاء عند امتناع المسحوب عليه وبذلك يمكن للحامل الرجوع على الملتزمين الصرفيين منفردين أو مجتمعين والمطالبة بقيمة الورقة التجارية سواء كان ذلك في ميعاد استحقاقها أم قبل ذلك الميعاد، فكل موقع عليها يكون مسؤولا على وجه التضامن مع الملتزمين الآخرين Solidarity is one of the principles of commercial law, and one of the most important guarantees adopted by the exchange law in order for the holder of the commercial paper to obtain its value when it is due, as the latter has the right to recourse to any signatory or to all signatories for the full value of the commercial paper. Commercial papers are considered a means of payment that takes the place of money in fulfillment. They perform the same function that money performs, and they are also negotiable. Given the importance of these papers in commercial transactions, and in order for them to actually take the place of money in fulfillment, the Algerian legislator has surrounded them with a set of guarantees to protect trust and credit. existing between merchants, and exchange solidarity is considered one of the most important of these guarantees. It protects the holder of the commercial paper and makes him feel safe and reassured, which makes every signatory of it a guarantor of payment in the event of the drawee’s refusal. Thus, the holder can return to the exchange obligors individually or jointly and claim the value of the commercial paper, whether that is on its maturity date or before that date. Each signatory of it is responsible. In solidarity with other committed people.

The Extent of Social Responsibility among Libyan and Palestinian Telecom Companies in Mitigating the Effects of the COVID-19 Pandemic - Rashwan, Abdelrahman; Amarif, Suad (Jordan Journal of Applied Science-Humanities Series, 2024)
This study primarily aims to identify the social responsibility of Libyan and Palestinian telecommunications companies and their contributions to addressing the negative effects resulting from COVID-19. The study focuses on the companies’ efforts to alleviate the burden on the state and citizens, exploring the most significant social contributions made by these companies in response to the pandemic. To answer the research questions and test the hypotheses, the researchers employed a descriptive and analytical approach. After obtaining the necessary data, a validated and evaluated questionnaire was distributed to a sample of 53 individuals, including financial managers, internal auditors, financial analysts, and accountants working in Libyan and Palestinian telecommunications companies. The results of the study indicated that Libyan telecom companies did not contribute significantly to mitigating the negative effects of COVID-19 by activating their social responsibility roles. This conclusion is supported by the respondents' answers, which reflected a moderate degree of contribution, with a mean value of 3.08 and a relative weight of 61.69%, along with a standard deviation of 0.85 and a significance level (Sig) of 0.686. Similarly, Palestinian telecom companies also did not significantly contribute to mitigating the negative effects of the COVID-19 pandemic through their social responsibility roles. Respondents’ answers indicated a moderate level of contribution, with a mean value of 3.24, a relative weight of 64.85%, a standard deviation of 0.849, and a significance level (Sig) of 0.256. The study recommends that Libyan and Palestinian telecommunications companies should enhance their social roles in mitigating the negative effects of the COVID-19 pandemic by actively implementing social responsibility initiatives.
Keywords: COVID-19 Pandemic; CSR; Corporate Communications; Corporate Social Responsibility; Libya; Telecom Company

التحكيم وفقًا لاتفاقية الأمم المتحدة بشأن نقل البضائع عن طريق البحر (هامبورغ، 1978) - Ghassan, ali; Haidara, jaber (Tishreen University journal of research and scientific studies -economic and legal sciences, 2024)
International maritime transport represents the backbone of international trade in our current era, for many reasons, such as low costs and the ability to transport large quantities of goods at once. The United Nations Convention on the Maritime Transport of Goods of 1978, known as the Hamburg Convention, represents a qualitative shift in regulating the rules of maritime transport of goods. Among the important topics regulated by the agreement is the subject of arbitration, as it is the most important means of settling disputes related to international trade contracts, especially the contract for the maritime carriage of goods. Accordingly, this research studies the rules of the Hamburg Convention related to arbitration as a means of settling disputes related to the contract for the maritime carriage of goods. يمثل النقل البحري الدولي عصب التجارة الدولية في عصرنا الحالي، ألسباب عديدة كانخفاض التكاليف والقدرة عمى والمعروفة 1978 نقل كميات كبيرة من البضائع دفعة واحدة، وتمثل اتفاقية األمم المتحدة لمنقل البحري لمبضائع لعام ىامبورغ، نقمة نوعية عمى صعيد تنظيم قواعد النقل البحري لمبضائع، ومن بين الموضوعات اليامة التي باسم اتفاقية نظمتيا االتفاقية، موضوع التحكيم، باعتباره أىم وسائل تسوية النزاعات المرتبطة بعقود التجارة الدولية، وخاصة عقد د اتفاقية ىامبورغ المتعمقة بالتحكيم كوسيمة لتسوية النزاعات النقل البحري لمبضائع، وبناء عميو يتناول ىذا البحث قواع ال
Keywords: Arbitration; Bill of lading; Bills of lading; Carriage of Goods by Sea (1978); Hamburg Convention; Hamburg Rules; International commercial arbitration; Maritime carriage contract; Maritime transport; UN Convention; اتفاقية ىامبورغ; التحكيم; سند الشحن; عقد النقل البحري

الحماية الجزائية للعالمة التجارية بين التشريع الجزائري و التشريع المغربي - دراسة مقارنة - صافو, سارة (Université d'Oran 2 Mohamed Ben Ahmed, 2024)
الملخص تهدف هذه الدراسة بتحميل ومقارنة الحماية الجزائية من الجرائم الماسة بالعالمة التجارية في الجزائر والمغرب، في هذا الصدد تهدف الدراسة إلى معرفة األهمية االقتصادية التي تكتسيها العالمة التجارية محل الحماية و أثر الجرائم الواقعة عميها عمى االقتصاد الوطني لمبمدين، خاصة في ظل اتجاه الجزائر والمغرب نحو تبني اقتصاد مبني عمى المعرفة القائم عمى اإلبداع واالبتكار. في البداية، وبعد التطرق لألحكام المنظمة لمعالمة التجارية من خالل توضيح مدى توافق التشريعين، تعني الد ارسة بتحميل ومقارنة طبيعة القانونية لمعالمة التجارية من ضبط مفهومها إلى اكتساب الحق فيها، عن طريق توضيح أهميتها كمؤشر لقياس االقتصاد الوطني. تنتقل الد ارسة لتبين تدخل المشرعين الج ازئري والمغربي بوضع آليات حمائية قبمية وبعدية لردع الج ارئم الواقعة عمى العالمة التجارية، تتفحص الدراسة هنا، دور اإلجراءات التحفظية ودعوى التقميد كآلية لحماية القانونية لمعالمة التجارية بهدف حماية االقتصاد الوطني. وانطالقا من القسمين السابقين لمدراسة، تحاول هذه األخيرة توضيح بعض التوجهات االقتصادية التي انتهجتها كل من الجزائر والمغرب من اقتصاد تقميدي إلى اقتصاد مبني عمى المعرفة، وأن اإلشكال المطروح في مثل هكذا ظروف جديدة يكمن في مدى ارتباط حماية العالمة التجارية بحماية االقتصاد الوطني، تبين الدراسة في هذا الشأن أن اختالف حماية التشريع الج ازئري لمعالمة التجارية عن التشريع المغربي يكمن في اختالف اقتصاد دولتين. نخمص إلى القول أن السياسة الردعية التي أقرها التشريعين الج ازئري والمغربي ال تتوافق مع طبيعة هذه الج ارئم الماسة باالقتصاد الوطني، حيث يجب تعديل العقوبات وتكييفها مع األوضاع االقتصادية الجديدة من خالل تشديدها. Abstract: The aim of this study is to analyse and compare the penal protection against crimes against the brand in Algeria and Morocco in this regard. The study aims to learn about the legal nature of the protected brand and the impact of these crimes on the national economy of the two countries, especially in view of Algeria's and Morocco's trend towards a knowledge-based economy based on creativity and innovation. Initially, after addressing the provisions governing the trademark by clarifying the compatibility of the two legislations, the study means analysing and comparing the legal nature of the trademark in question from the control of its concept to the acquisition of the right to it, by clarifying its importance as an indicator of measurement of the national economy. The study goes on to show the intervention of Algerian and Moroccan legislators by establishing tribal and remote protectionist mechanisms to deter crimes against the trademark. The study examines here the role of provisional measures and the case for tradition as a mechanism for protecting the legal protection of the trademark in order to protect the national economy. The study goes on to show the intervention of Algerian and Moroccan legislators by establishing tribal and remote protectionist mechanisms to deter crimes against the trademark. The study examines here the role of provisional measures and the case for tradition as a mechanism for protecting the legal protection of the trademark in order to protect the national economy. Based on the previous two sections of the study, the latter attempts to clarify some of the economic trends adopted by Algeria and Morocco, from an economy based on quarters to an economy based on knowledge, and that the problem presented in such new circumstances lies in the extent to which protecting the trademark is linked to protecting the national economy. The study shows In this regard, the difference in Algerian trademark protection from Moroccan legislation lies in the difference in the economies of the two countries.We conclude by saying that the deterrent policy adopted by Algerian and Moroccan legislation is incompatible with the nature of these crimes, which affect the national economy. The penalties must be adjusted and adapted to the new economic conditions by tightening them. Résumé : Cette étude a pour objet le problème de la protection pénale de la marque commerciale en Algérie et au Maroc. Elle vise à faire connaitre l’importance économique de la marque protégée et l’impact économique des crimes dans les deux pays compte tenu de la tendance de ces deux pays à adopter une économie de créativité et d’innovation. L’étude consiste en la comparaison et en l’analyse juridique de la marque de l’adaptation de son concept à l’acquisition du droit à celle –ci après clarification de son importance en tant qu’indicateur de mesure de l’économie nationale. L’étude montre ensuite l’impact des législation algériennes et marocaines qui établissent des mécanismes visant à la protection à distance afin de dissuader tout crime contre la marque. Le rôle des mesures provisoires et aussi examine dans cette étude ainsi que l’action en contrefaçon en tant que moyen de protection juridique de la marque. Afin que protéger l’économies nationale. En outre, cette étude essaye d’illustrer certaines des tendances économiques algériennes d’une économie basée sur la rente vers une économie basée sur le savoir (créativité et innovation). Dans ces nouvel es circonstances, la protection des marques et liée à la protection de l’économie nationale. A cet égard, la protection de la marque commerciale en Algérie diffère de celle du Maroc du fait de la différence des économies des deux états algériens et marocains. Nous concluons que la politique de dissuasion adoptée par les législations algérienne et marocaine est incompatible avec la nature de ces crimes, qui affectent l’économie nationale. Les sanctions doivent être ajustées et adaptées aux nouvelles conditions économiques en les resserrant.
Keywords: Action pénale; Contrefaçon; Criminal case; Droit algérien; Droit marocain; Enregistrement; Fake; Marque commerciale; Mesures conservatoires; Procedures conservatory; Protection pénale; Registry; Trademark

الأعوان التجاريون لعملية النقل البحري - قزدعلي, أسماء (Université d'Oran 2 Mohamed Ben Ahmed, 2024)
الملخص : نظم القانون البحري الجزائري مهام و مسؤوليات كل من وكيل السفينة ووكيل الحمولة في المواد من 609 إلى 630 أما السمسار البحري فمن المادة 631 إلى المادة 639 ، فتعتبر هذه الأنشطة وليدة خوصصة النشاطات البحرية التي كانت محتكرة من قبل الدولة سابقا بالإضافة إلى ما أصبحت عليه السفن التجارية و تكاليفها الباهضة . كان ربان السفينة هو من يتولى القيام بهذه الأنشطة ذلك لحساب المجهز أو المرسل إليه ، فاقتضى الأمر إعفاءه منها ذلك نظرا لبقاء السفينة في الميناء مدة طويلة والبحث عن شخص طبيعي أو معنوي في كل ميناء يقوم لحساب المجهز أو المرسل إليه بتسليم البضائع وحراستها و المحافظة عليها و تحصيل الأجر عن ذلك . وعليه أصبح الأعوان التجاريون هم من يتولون القيام بهذه الأنشطة و المهام وذلك بناءا على عقد تنجر عنه جملة من الالتزامات و المسؤوليات على عاتق طرفاه . Le droit maritime algérien réglemente les fonctions et les responsabilités de consignataire du navire et de consignataire de cargaison dans les articles de 609 à 630. Le courtier naval de l’article 631 à l’article 639 considère ces activités comme la naissance de la privatisation des activités maritimes précédemment monopolisées par l’État en plus de ce que sont devenus les navires commerciaux et leurs coûts exorbitants. C’est le capitaine du navire qui a effectué ces activités au nom du transformateur ou du destinataire. Cela était rendu nécessaire par l’exemption, compte tenu du long séjour du navire au port et de la recherche d’une personne physique ou morale dans chaque port pour lequel le transformateur ou le destinataire livrait, gardait, entretenait et percevait les salaires. En conséquence, ce sont les agents commerciaux qui exercent ces activités et fonctions sur la base d’un contrat qui remplit un certain nombre d’obligations et de responsabilités des deux parties. Algerian maritime law regulates the duties and responsibilities of the ship’s agent and cargo agent in the section from 609 to 630. The naval broker from section 631 to section 639 considers these activities to be the birth of the privatization of maritime activities previously monopolized by the State in addition to what has become of commercial vessels and their exorbitant costs. The master of the vessel performed these activities on behalf of the processor or consignee. This was made necessary by the exemption, taking into account the vessel’s long stay in port and the search for a natural or legal person in each port for which the processor or consignee delivered, kept, maintained and collected wages. Consequently, it is the commercial agents who carry out these activities and functions on the basis of a contract which fulfils a number of obligations and responsibilities of both parties.
Keywords: Agency contract; Consignataire de cargaison; Consignataire de navire; Contrat de transport maritime; Contrat d’agence; Courtier maritime; Droit algérien; Droit maritime; Navire; Payload agent; Sea broker; Sea transport contract; Ship agent

الصفقات العمومية التي يبرمها أشخاص القانون الخاص في التشريع الجزائري مقارنا - كوثر, بن ملوكة (Université d'Oran 2 Mohamed Ben Ahmed, 2024)
الملخص يحظى مجال الصفقات العمومية بأهمية بالغة بالنسبة للاقتصاد الوطني، وتعود هذه الأهمية لاعتبار الصفقة العمومية الطريق القانوني الذي تستخدمه الدولة ومختلف المتعاملين من أجل انجاز المشاريع بجودة عالية بأقل التكاليف وآجال مدروسة، وكون تمويل الصفقات العمومية يعود للخزينة العامة للدولة وجب توفير الحماية القانونية لهذه العملية عن طريق إيجاد تنظيم قانوني خاص بها يحقق المصلحة العامة ويحترم الحرية الاقتصادية في ذات الوقت، وهو ما جسده المشرع الجزائري عمليا بإصدار المرسوم الرئاسي 15-247 الذي عرف عدة تعديلات سابقة ومواكبة لمتطلبات كل مرحلة، فالقول بالصفقة العمومية يحيل بالضرورة إلى أشخاص القانون العام أي الدولة والمؤسسات التابعة لها والقول بغير ذلك نوع من التضاد. لكن المشرع ألزم أشخاص القانون الخاص الخاضعين للتشريع التجاري بتطبيق أحكام التنظيم الصفقات العمومية في حالات محددة وهي التمويل الكلي أو الجزئي للصفقة من الخزينة العمومية (الدولة أو الجماعات الإقليمية) ما يخلق اشكال أي قانون يطبق في حالة النزاع وبالنتيجة أي هرم قضائي هو المختص في البت في منازعة أحد أطرافها أشخاص القانون الخاص ،وكذا حالات التمويل وتجسيدها عمليا، اضافة إلى دور الوسائل الودية المنصوص عليها في كل من تنظيم الصفقات العمومية أو قانون الإجراءات المدنية في حل المنازعات وتجسيد المشاريع واقعيا. Résumé Le domaine des marchés publics occupe une grande place dans l’économie nationale ; cela est dû au fait qu’un marché public est considéré comme la voie légale utilisée par l’État et les différents partenaires pour réaliser des projets au moindre coût et dans des délais raisonnés. Comme le financement des marchés publics relève du Trésor public, l’état est tenu d’assurer la protection juridique de ce processus en créant sa propre organisation juridique dans l’intérêt public tout en respectant la liberté économique, c’est ce que le législateur algérien a matérialisé, dans la pratique, par la promulgation du décret présidentiel n°15-274 qui a connu plusieurs modifications aux fins de de répondre aux exigences de chaque étape. Dire « Marché Public » renvoie nécessairement aux entités du droit commun, à savoir, l’état et ses institutions et affirmer les choses autrement serait une forme de contradiction. Toutefois, le législateur a engagé les entités du droit privé soumis à la législation commerciale dans l’application des dispositions de la réglementation des marchés publics dans un cas spécifique, à savoir, le financement total ou partiel du marché à partir du trésor public (États et/ou collectivités territoriales) ; de cela est issue une loi applicable en cas de conflit, avec pour conséquence, toute pyramide judiciaire compétente pour statuer sur un litige relevant en partie du droit privé, dans les cas de leur financement et matérialisation pratique, ainsi que lorsqu’il s’agit du rôle des moyens de règlement à l’amiable prévus aussi bien par la réglementation des marchés publics que par le Code de procédure civile dans la résolution des litiges et la réalisation concrète des projets. Abstract The field of public procurement occupies a major place in the national economy; this is due to the fact that a public procurement is considered to be the legal way used by the State and the various partners to carry out projects at the lowest cost and within reasonable deadlines. As the financing of public procurement is the responsibility of the Treasury, the State is required to ensure the legal protection of this process by creating its own legal organization in the public interest while respecting economic freedom, this is what the Algerian legislator materialized, in practice, by the promulgation of presidential decree No. 15-274 which has undergone several modifications in order to meet the requirements of each stage. To say "Public Procurement" necessarily refers to the entities of common law, namely, the state and its institutions and to affirm things otherwise would be a form of contradiction. However, the legislator has committed the private law entities subject to commercial law to apply the provisions of the public procurement regulation in a specific case, namely, the total or partial financing of the contract from the public treasury (States and/or territorial authorities); from this comes a law applicable in case of conflict, with the consequence, any judicial pyramid competent to rule on a dispute falling partly under private law, in cases of their financing and practical materialization, and when it concerns the role of the means of amicable settlement provided for by the regulation of public contracts as well as by the Code of Civil Procedure in the resolution of disputes and the concrete implementation of projects.
Keywords: Commercial and public company; Conflict of judicial compétences; Conflit des compétences judiciaires; Entreprise publique Industrielle; Entreprise publique commerciale; Financement par le trésor; Financing by treasury; Industrial public company; Marché; Market; Means of amicable settlement; Moyens de règlement à l’amiable